Electrochemical synthesis and functional properties of metal and alloy-based composition coatings - Zelele, Daniel M.; Rutkowska-Gorczyca, Malgorzata (Recent Contributions to Physics, 2024)
This work presents a comprehensive review on the electrochemical synthesis and functional properties of metal and alloy-based composition coatings. Nowadays, electrochemical synthesis is considered a versatile and widely used technique for producing metal and alloy coatings with precisely controlled composition, thickness, and microstructure. These coatings offer a variety of functional properties that can enhance the performance and durability of various substrates. It typically involves immersing a substrate (cathode) in an electrolytic solution containing dissolved metal ions. A current is applied between the cathode and an anode, causing the metal ions to be reduced and deposited onto the cathode surface as a coating. The specific properties of the coating, such as composition, thickness, and morphology, can be controlled by various parameters, including electrolyte composition, current density and potential, temperature and pH as well as substrate material and pretreatment. The utilization of electrochemical methods in coating fabrication has gained significant attention due to their efficiency, precision, and environmental friendliness. As such, the focus of this review is on the synthesis processes, structural characterization, and functional properties of coatings comprising various metals and alloys to help understand electrochemical deposition techniques for tailored coatings with enhanced properties for diverse applications by summarizing previous studies.